Statutory elements of the crime of motor vehicle registration plates forgery (Ius Novum, 2024)
The article is of a scientific and research nature and its subject are the crimes defined in Article 306c of the Penal Code, in force from October 1, 2023, regarding, among others, counterfeiting or altering in order to use a motor vehicle registration plate as an authentic one (§ 1) and using it as an authentic one (§ 2). The basic research goal was to assess the validity of introducing this provision into the Penal Code and the correctness of determining the conditions for its application and its scope. The assumption was that criminalizing such behaviour could be an effective weapon in the fight against the phenomenon of fuel theft at gas stations, because the perpetrators of these thefts usually supply fuel to their vehicles. The analysis included the subject of protection of this provision, the types of crimes, their features such as counterfeiting, alteration, the concept of a license plate, legalization of the plate, the purpose of the causative behaviour and the concept of a motor vehicle. To analyse this issue, it was enough to use the normative and dogmatic method.
Keywords: alteration, counterfeiting, legalization, license plate, motor vehicle, subject of protection, types of crime